2002
DOI: 10.2174/0929867023371247
|View full text |Cite
|
Sign up to set email alerts
|

Okadaic Acid, Useful Tool for Studying Cellular Processes

Abstract: One of the most interesting groups of substances of marine origin, from structural and pharmacological points of view are polyether toxins, which generally present a great diversity in size and potent biological activities. The subject of this review is limited to okadaic acid (OA). It was the first example of a group of polyether toxins produced by marine microalgae, which is responsible for the natural phenomena known as Diarrhetic Shellfish Poisoning, DSP red tides. These toxins are accumulated in the diges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
72
0
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(79 citation statements)
references
References 0 publications
3
72
0
2
Order By: Relevance
“…Calyculin A inhibits protein phosphatase 1 (PP1; IC 50 0.3-0.7 nM) and protein phosphatase 2a (PP2a; IC 50 0.2-1 nM) at similar concentrations (Fernandez et al, 2002). However, ϳ50-fold higher concentrations of okadaic acid are required to inhibit PP1 (IC 50 20 nM) compared with PP2a (IC 50 0.2-1 nM).…”
Section: Figure 3 Time Course Of Cpeb Phosphorylation In Neurons Stimentioning
confidence: 99%
See 1 more Smart Citation
“…Calyculin A inhibits protein phosphatase 1 (PP1; IC 50 0.3-0.7 nM) and protein phosphatase 2a (PP2a; IC 50 0.2-1 nM) at similar concentrations (Fernandez et al, 2002). However, ϳ50-fold higher concentrations of okadaic acid are required to inhibit PP1 (IC 50 20 nM) compared with PP2a (IC 50 0.2-1 nM).…”
Section: Figure 3 Time Course Of Cpeb Phosphorylation In Neurons Stimentioning
confidence: 99%
“…However, ϳ50-fold higher concentrations of okadaic acid are required to inhibit PP1 (IC 50 20 nM) compared with PP2a (IC 50 0.2-1 nM). Neither phosphatase inhibitor has any significant effect on calcineurin, PP2b (Fernandez et al, 2002). We took advantage of these protein phosphatase inhibitors and their IC 50 values to identify the protein phosphatase that regulates CPEB in hippocampal neurons.…”
Section: Figure 3 Time Course Of Cpeb Phosphorylation In Neurons Stimentioning
confidence: 99%
“…The results showed that with control incubation, tau was dephosphorylated at Thr212, Ser262, and Ser396 by protein phosphatases, while OA, a potent protein phosphatase inhibitor, prevented the dephosphorylation of tau at 10 nmol/L, a concentration that only inhibits PP2A [19] .…”
Section: Pp2a In Vitromentioning
confidence: 96%
“…In vitro, tau is gradually dephosphorylated by many serine/threonine protein phosphatases, of which PP2A contributes the major part [7] . OA is a potent inhibitor of protein phosphatase, and only inhibits PP2A when used at 10 nmol/L in vitro [19] .…”
Section: Pp2amentioning
confidence: 99%
“…4, lanes 3-5). These data suggested that Evans Blue, Chicago Sky Blue, and Oxamine Blue can be effectively incorporated into cells to [24,25]. For PPM phosphatases, however, only two compounds have been so far reported as specific inhibitors.…”
Section: Effects Of the Inhibitors On The Phosphatase Activity Of Cammentioning
confidence: 99%